Pretreatment attrition and treatment initiation delay among rifampicin-resistant tuberculosis patients in Lagos, Nigeria: a retrospective cohort study. (16th June 2022) - Adejumo, Olusola A; Daniel, Olusoji; Adepoju, Victor A; Onoh, Moses O; Sokoya, Olusola D; Abdur-Razzaq, Hussein; Moronfolu, Olanike; Oyadotun, Omolara M; Olusola-Faleye, Bolanle
Abstract: Background: Assessing associated factors of pretreatment attrition and treatment delays among rifampicin-resistant tuberculosis (RR-TB) patients could serve as a valuable tool to control and prevent its community spread. We assessed the factors associated with pretreatment attrition and treatment initiation delays among RR-TB patients in Lagos, Nigeria. Methods: A retrospective cohort study was conducted involving secondary program data of RR-TB patients diagnosed using the Xpert MTB/RIF assay and initiated on treatment between 1 January 2015 and 31 December 2017 in Lagos. Factors associated with pretreatment attrition and treatment initiation delay were determined using logistic regression. Results: Of the 606 RR-TB patients diagnosed during the review period, 135 (22.3%) had pretreatment attrition. Previously treated TB patients had a 2.4-fold greater chance of having pretreatment attrition than new RR-TB patients (adjusted odds ratio 2.4 [95% confidence interval 1.2–5.0]). The median time to treatment initiation was 29 d (interquartile range [IQR] 18–49). It was longer for new RR-TB patients (49 d [IQR 36–59]) than previously treated TB patients (28 d [IQR 17–44]). A total of 47% had long treatment delays. Being newly diagnosed with RR-TB was associated with long treatment delays. Conclusions: The pretreatment attrition rate and proportion of RR-TB patients with treatment delays were high. Pragmatic approaches to address the high pretreatment attrition and treatment delays in Lagos, Nigeria, are urgently needed.